Sampling frequency and eye-tracking measures: how speed affects durations, latencies, and more - Richard Andersson; Marcus Nyström; Kenneth Holmqvist (Bern Open Publishing, 2010)
We use simulations to investigate the effect of sampling frequency on common dependent variables in eye-tracking. We identify two large groups of measures that behave differently, but consistently. The effect of sampling frequency on these two groups of measures are explored and simulations are performed to estimate how much data are required to overcome the uncertainty of a limited sampling frequency. Both simulated and real data are used to estimate the temporal uncertainty of data produced by low sampling frequencies. The aim is to provide easy-to-use heuristics for researchers using eye-tracking. For example, we show how to compensate the uncertainty of a low sampling frequency with more data and postexperiment adjustments of measures. These findings have implications primarily for researchers using naturalistic setups where sampling frequencies typically are low.